Impact of the gut-lung axis on tuberculosis susceptibility and progression - Enjeti, Aditya; Sathkumara, Harindra Darshana; Kupz, Andreas (Frontiers in Microbiology, 2023)
Tuberculosis (TB) has remained at the forefront of the global infectious disease burden for centuries. Concerted global efforts to eliminate TB have been hindered by the complexity of Mycobacterium tuberculosis (Mtb), the emergence of antibiotic resistant Mtb strains and the recent impact of the ongoing pandemic of coronavirus disease 2019 (COVID19). Examination of the immunomodulatory role of gastrointestinal microbiota presents a new direction for TB research. The gut microbiome is well-established as a critical modulator of early immune development and inflammatory responses in humans. Recent studies in animal models have further substantiated the existence of the 'gut-lung axis', where distal gastrointestinal commensals modulate lung immune function. This gut microbiome-lung immune crosstalk is postulated to have an important correlation with the pathophysiology of TB. Further evaluation of this gut immunomodulation in TB may provide a novel avenue for the exploration of therapeutic targets. This mini-review assesses the proposed mechanisms by which the gut-lung axis impacts TB susceptibility and progression. It also examines the impact of current anti-TB therapy on the gut microbiome and the effects of gut dysbiosis on treatment outcomes. Finally, it investigates new therapeutic targets, particularly the use of probiotics in treatment of antibiotic resistant TB and informs future developments in the field.